(untitled) (Bangladesh Journal of Medical Science, 2024)
Plagiarism is one of the most prevalent forms of misconduct in the academic scenario. In recent years, scientific misconduct and academic dishonesty have been in the focus of interest of the academic and scientific community. Objective Due to the rise in research work in academic institutions, its imperative that all who are involved in research should have knowledge about plagiarism. This is a cross-sectional survey study, done on medical students to find out their attitudes toward plagiarism. Materials and methods The study was conducted at RAK Medical and Health Sciences University (RAKMHSU), UAE, using Attitude toward Plagiarism (ATP) questionnaire. The participants were from MBBS 3, 4 and 5th years. After the ethical committee clearance, the questionnaire was implemented to students in their free time. The duration given for filling the questionnaire was about 5 to 10 mins. Results Response rate was 66% (N=169). Results revealed moderate scores for positive attitude questions, negative attitude questions, and subjective norms among the three years towards plagiarism. There was no significant difference between the years of study or gender of the students in the group scores. However, the attitude of year-3 students showed a significant positive correlation with year-5 students (p<0.05). Conclusion The result reflects that the students’ attitudes towards plagiarism are divided. The teaching of ethics should be a part of the curriculum and it should be reinforced with workshops and CMEs. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 706-713